2002
DOI: 10.1016/s1097-2765(02)00542-7
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Variant H3.3 Marks Active Chromatin by Replication-Independent Nucleosome Assembly

Abstract: Two very similar H3 histones-differing at only four amino acid positions-are produced in Drosophila cells. Here we describe a mechanism of chromatin regulation whereby the variant H3.3 is deposited at particular loci, including active rDNA arrays. While the major H3 is incorporated strictly during DNA replication, amino acid changes toward H3.3 allow replication-independent (RI) deposition. In contrast to replication-coupled (RC) deposition, RI deposition does not require the N-terminal tail. H3.3 is the exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
925
1
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,035 publications
(982 citation statements)
references
References 61 publications
47
925
1
9
Order By: Relevance
“…Enrichment of H3.3 has been linked with transcriptional activity and indeed has been proposed to contribute to ensuring that full transcription is maintained through cell division (Ahmad & Henikoff, 2002). However, we recently showed that surprisingly few genes exhibit significantly dysregulated expression in DT40 cells lacking H3.3 (Frey et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment of H3.3 has been linked with transcriptional activity and indeed has been proposed to contribute to ensuring that full transcription is maintained through cell division (Ahmad & Henikoff, 2002). However, we recently showed that surprisingly few genes exhibit significantly dysregulated expression in DT40 cells lacking H3.3 (Frey et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, the apparent inconsistency in this idea is merely an extension of an existing paradox. Specifically, HIRA and its orthologs in other species are typically involved in gene silencing and formation of heterochromatin (13,50,64,67,97,116,117,119,123), whereas HIRA's favored deposition substrate, histone H3.3, is linked to transcriptional activation (3,77,80,112,133). However, to our knowledge, histone H3.3 per se has not been shown to directly cause or contribute to transcription activation, and a proportion of histone H3.3 does carry posttranslational marks characteristic of transcriptionally silent chromatin (55,74,77).…”
Section: Chromosome Condensation Is Driven By Histone Chaperones Hiramentioning
confidence: 92%
“…Unfortunately, because human histone H3.3 and canonical H3.1 only differ by 5 amino-acids, differentiating between them immunologically is challenging, making it difficult to ask whether endogenous histone H3.3 is specifically enriched in SAHF. The idea that SAHF contains histone H3.3 may initially seem unlikely, because deposition of histone H3.3 is typically linked to transcription activation (3,77,80,112,133), whereas SAHF is a form of transcriptionally silent facultative heterochromatin (87,88,145). However, the apparent inconsistency in this idea is merely an extension of an existing paradox.…”
Section: Chromosome Condensation Is Driven By Histone Chaperones Hiramentioning
confidence: 99%
“…This scenario attracted significant attention, raising the questions of whether and to what extent tetramer splitting occurs, at which genomic regions, and during which replication-dependent or -independent processes (1-3, 11). This issue is also affected by the fact that many organisms have distinct H3 variants that are deposited during DNA replication (H3.1) or independently of DNA replication (H3.3) by different deposition machineries (12).A recent analysis, published during the last stages of the present work, showed that all of the canonical H3.1 and most of the variant H3.3 in a human cell line are incorporated by the conservative assembly model, consistent with earlier observations (13). However, a minor fraction of H3.3 is present in mixed old-new tetramers, indicating that tetramer splitting is specific to the H3 variant that incorporates outside of replication.…”
mentioning
confidence: 99%